Enhancing The Role of Native Speaker and Non-Native Speaker English Teachers in Indonesia - Widya Febrina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
There has been a growing debate on the differences between native speaker and non-native speaker teachers in English language teaching in Indonesia. The issue of native-speakerism has put non-native teachers in the corner where they feel inferior over native teachers. This native-speakerism issue then make the students and language institution favour the native speakers more than the local teachers. Thus, this research aims to investigate the role of both native and non-native English teachers in Indonesia. This study employs a qualitative literature review method, drawing on scholarly articles, books, and academic publications related to English as a Lingua Franca, and native-speakerism. The data were collected through systematic analysis of relevant literature from reputable academic databases. The findings indicate that the distinction between native and non-native English speakers remains influential but is gradually being redefined. Both native and local teachers have their own strengths and weaknesses. Native speakers teacher may have some benefits on language teaching, however, marginalizing the non-native teacher is also not a good idea. Recognizing the legitimacy and contributions of non-native speakers is essential for developing more inclusive and realistic approaches to English language use and education in a globalized world.